Social structure and social policy: about the institutional flexibility of three modern welfare states - Foschi, Matteo; Schommer, Martin (Luxembourg, 2008)
"This paper addresses the question of the institutional flexibility of three major European welfare states. Using Data from the second and fifth wave of the Luxembourg Income Study (LIS), we measure first how effectively the German, British and Italian welfare state have responded changes in their country-specific poverty risks profile. Further, we apply a macro-simulation to evaluate the performance of the three welfare states in terms of poverty reduction. We find that the social policy institutions of Germany and Britain are more able to deal successfully with changing age and household structures as the Italian welfare state."